Preparation of rambutan-like Co0.5Ni0.5Fe2O4 as anode for high–performance lithium–ion batteries - Wang, Qian; Wu, Yongzi; Pan, Ning; Yang, Chenyu; Wu, Shuo; Li, Dejie; Gu, Shaonan; Zhou, Guowei; Chai, Jinling (Frontiers in Chemistry, 2022)
NiFe2O4 is a kind of promising lithium ion battery (LIB) electrode material, but its commercial applications have been limited due to the electronic insulation property and large volume expansion during the conversion reaction process, which results in rapid capacity decrease and poor cycling stability. We synthesized rambutan-like Co0.5Ni0.5Fe2O4 using the self-templating solvothermal method. The special structure of Co0.5Ni0.5Fe2O4 which was formed by the assembly of numerous nanosheets could effectively buffer the volume change during the charging and discharging process. Partial substitution of Ni with Co. in NiFe2O4 leads to Co0.5Ni0.5Fe2O4, the coexisting of both nickel and cobalt components is expected to provide more abundant redox reactions. The specific capacity of the rambutan-like Co0.5Ni0.5Fe2O4 as an anode material for LIB could reach 963 mA h g−1 at the current density of 500 mA g−1 after 200 cycles, confirming that the as-synthesized material is a promising candidate for LIBs.